An Incremental Approach to Porting Complex Scientific Applications to GPU/CUDA - Delgado, Javier; Gazolla, João; Clua, Esteban; Sadjadi, S. Masoud (Anais do Brazilian e-Science Workshop (BreSci); 2010: Anais do IV e-Science Workshop, 2010)
This paper proposes and describes a developed methodology to port complex scientific applications originally written in FORTRAN to the nVidia CUDA. The process was developed and validated by porting an existing FORTRAN weather and forecasting algorithm to a GPU parallel paradigm. We believe that the proposed porting methodology described can be successfully utilized in several other existing scientific applications.